Enhancement mechanisms of Anions production in a magnetized sheet plasma source - Noguera, Virginia R.
A magnetized sheet plasma negative ion source (MSPNIS) is modified for optimized and enhanced H- ion production. First, a set of permanent ferrite magnets is installed at the production chamber in a hexapole multicusp configuration. This resulted to decreased power requirements, improved plasma confinement and longer filament lifetime. By this, a wider choice of discharge currents for sustained quiescent plasmas is made possible. Second, the method of adding argon to the hydrogen plasma similar to the scheme in [1] was performed to find the optimum conditions for H- formation and extraction. Using an E×B probe, H-yields were investigated at varied argon-hydrogen admixtures, different discharge currents and spatial points relative to the core plasma. The optimum H- current density extracted at 3.0 cm from the plasma core using 3.0 A plasma current with 10% argon seeding increased by a factor of 2.42 (0.63 A/m2) compared to the measurement of reference 1. Third, the argon-hydrogen plasma at the extraction chamber is seeded with magnesium. Mg disk with an effective area of 22 cm2 is placed at the extraction region?s anode biased 175 V with respect to the cathode. With Mg seeding, the optimum H-current density at the same site and discharge conditions increased by 4.9 times (3.09 A/m2). The enhancement effects were analyzed vis-à-vis information gathered from the usual Langmuir probe (electron temperature and density), electron energy distribution function (EEDF) and the ensuing dissociative attachment (DA) reaction rates at different spatial points for various plasma discharges and gas ratios. Investigations on the changes in the effective electron temperature and electron density indicate that the enhancement is due to increased density of low-energy electrons in the volume, conducive for dissociative attachment reactions. With Mg, the density of electrons with electron temperature of about 3eV is increased by 3 orders of magnitude from 2.76x1012 m-3 to 2.90x1015 m-3. The effects of seeding on the average energy, velocity and the mean lifetime of the formed ions are also calculated from the measured electron energy distribution functions for a set of plasma conditions. The insights of these parameters may be relevant to ion beam applications. Several relevant mechanisms for the formation and destruction of H-ions are highlighted. PACS: 52.25.Xz; 52.50.Dg; 29.25.Ni; 52.70.Nc; 52.20.Hv; 52.25.Jm Keywords: Magnetized sheet plasma; Hydrogen negative ions; Rovibrational excitation; Dissociative attachment; Atomic processes; Molecular processe